Gold coated iron phosphide core–shell structures. Issue 42 (15th May 2017) - Kelly, Anna T.; Filgueira, Carly S.; Schipper, Desmond E.; Halas, Naomi J.; Whitmire, Kenton H.
Abstract : Core–shell Fe2 P@Au particles were made from Fe2 P particles by reaction with (1) γ-aminobutyric acid, (2) Au seeds and (3) HAuCl4 (aq.) and H2 CO or CO with shells up to 65 ± 21 nm. Increasing shell thickness gave a red shift in the plasmonic resonance. Abstract : Core–shell particles Fe2 P@Au have been prepared beginning with Fe2 P nanorods, nanocrosses and nanobundles prepared from the solvothermal decomposition of H2 Fe3 (CO)9 (μ3 -P t Bu). Iron phosphide structures can be produced from a single-source organometallic precursor with morphological control by varying the surfactant conditions to yield fiber bundles and dumbbell-shaped bundles ranging from nanometers to microns. Derivatization of the surfaces with γ-aminobutyric acid was used to attach Au nanoparticle seeds to the surface of the Fe2 P nanoparticles followed by completion of the Au shell by reduction with formaldehyde or aqueous HAuCl4 /CO, with the latter giving somewhat better results. Shell thickness ranged from an incomplete, partially coated Au shell to a thickness of 65 ± 21 nm by varying the amount of gold decorated precursor particles. Increasing the thicknesses of the Au shells produced a redshift in the plasmonic resonance of the resulting structures as was observed previously for FeO x @Au.